A BACwards glance at neurodegeneration: molecular insights into disease from LRRK2, SNCA and MAPT BAC-transgenic mice. (20th July 2011) - Johnson, Sara J.; Wade-Martins, Richard
Abstract : BAC (bacterial artificial chromosome)-transgenic mice expressing a transgene from an entire genomic locus under the control of the native promoter offer the opportunity to generate more accurate genetic models of human disease. The present review discusses results of recent studies investigating PD (Parkinson's disease) and tauopathies using BAC-transgenic mice carrying either the LRRK2 (leucine-rich repeat kinase 2), α-synuclein ( SNCA ) or MAPT (microtubule-associated protein tau) genes. In all lines, expression of the WT (wild-type) gene resulted in physiologically relevant protein expression. The effect of expressing the mutant form of a gene varied depending on the mouse strain or the particular disease mutation used, although it was common to see either neurochemical or behavioural differences in these animals. Overall, BAC technology offers an exciting opportunity to generate a wide range of new animal models of human-disease states.